Isolated disease of left anterior descending coronary artery. Angiocardiographic and clinical study of 218 patients. Issue 1 (January 1982) - Brooks, N; Cattell, M; Jennings, K; Balcon, R; Honey, M; Layton, C
Abstract : The angiocardiographic and clinical findings in 218 patients with significant obstruction confined to the left anterior descending coronary artery were reviewed to study the influence of the site of obstruction and of the collateral circulation on clinical presentation and prognosis. One hundred and fifty-six patients had been managed medically, 51 had had aortocoronary bypass operations, and 11 had had left ventricular aneurysms excised. The artery was divided into three segments: left anterior descending 1 (LAD1) from its origin to the first septal branch, left anterior descending 2 (LAD2) from the first septal to the first diagonal branch, and left anterior descending 3 (LAD3) the remaining distal vessel. Cardiogenic shock occurred only in patients with LAD1 lesions, but apart from this the clinical presentation bore no consistent relation to the site of disease. Patients with proximal lesions were more likely to have a "positive" exercise test, had more severely impaired left ventricular function, and had a worse prognosis than those with more distal disease. Non-visualisation of collateral vessels in patients with left anterior descending occlusion was associated with extensive infarction, and patients who presented with infarction had more severely impaired ventricular function than those who presented with angina and subsequently had an infarction. Left ventricular function was poor at the time of angiography in 11 of 12 of those who subsequently died; it is therefore unlikely that the prognosis of patients with isolated left anterior descending obstruction could be improved by expanding the indication for aortocoronary bypass from that of severe angina.